PENGARUH INFLUENCER DAN ONLINE CUSTOMER REVIEW TERHADAP PEMBELIAN IMPULSIF PADA PRODUK KOSMETIK HALAL DI TIKTOK SHOP - Ishmah Azizah Dwi Putri; Khusnul Fikriyah (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to determine the effect of influencers and online customer reviews on impulsive purchases of halal cosmetic products at the TikTok Shop. Using primary data sources through distributing questionnaires to TikTok Shop users. The sampling technique used non-probably sampling with purposive sampling technique. The data analysis technique in this study used the Structural Equation Model (SEM) with the SMART PLS 3.0 application. The results of this study indicate that there is a positive and significant influence between influencers on impulse purchases with a T-statistic value of 5.499 > T-table of 0.05. Then, online customer reviews influence impulsive purchases positively and significantly with a T-statistic value of 7.505 > T-table 0.05.